Характеристика уровня реактивной и личностной тревожности у беременных с невынашиванием в ранних сроках - Сюсюка, В. Г.; Плотник, В. А.; Syusyuka, V. G.; Plotnik, V. A.; Сюсюка, Володимир Григорович; Плотник, Володимир Олександрович (My University, 2015)
На основании проведенного исследования психологического состояния 67 беременных с клиникой угрожающего аборта, установлено, что уровень реактивной тревожности был статистически достоверно (p < 0,01) выше соответствующего показателя группы контроля, что может свидетельствовать о психоэмоциональной дезадаптации. При этом уровень личностной тревожности в группе беременных с невынашиванием в 5,5 раза превышал соответствующий показатель группы контроля. Based on the study of psychological state of sixty-seven pregnant women with threatening abortion clinic, found that levels of reactive anxiety was statistically significant (p < 0.01) higher than control group had, which may indicate a psychoemotional disadaptation. The level of personal anxiety in pregnant women with recurrent pregnancy loss in 5.5 times exceeded the corresponding indicator of the control group.
Characteristic of reactive and personal anxiety level in pregnant women with miscarriage in early pregnancy